2020
DOI: 10.1002/2211-5463.12991
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin alleviates bone damage by modulating protein expression and tissue redox state

Abstract: Here, we show that gastrodin, which is extracted from Gastrodia and has anti‐cell death, antiapoptosis and antioxidative activities, can reverse fluoride‐induced bone injury and apoptosis in a dose‐dependent way. This protective effect of gastrodin is likely to be exerted via inhibiting oxidative stress. Therefore, gastrodin may have potential for future development into a possible treatment for fluorosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…GAS has been widely reported to exhibit beneficial effects in a variety of neurological diseases and psychiatric disorders, such as Alzheimer's disease, Parkinson's disease and affective disorders, by inhibiting oxidation, inflammation and apoptosis, suppressing microglial activation and regulating mitochondrial cascades (35). Although a previous study revealed the protective effect of GAS on bone-related diseases (36), research into the specific effects and underlying mechanisms of action of GAS in LPS-induced hPDLSC injury is unknown to the best of our knowledge. The present study demonstrated that GAS could protect hPDLSCs against LPS-induced decrease in cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…GAS has been widely reported to exhibit beneficial effects in a variety of neurological diseases and psychiatric disorders, such as Alzheimer's disease, Parkinson's disease and affective disorders, by inhibiting oxidation, inflammation and apoptosis, suppressing microglial activation and regulating mitochondrial cascades (35). Although a previous study revealed the protective effect of GAS on bone-related diseases (36), research into the specific effects and underlying mechanisms of action of GAS in LPS-induced hPDLSC injury is unknown to the best of our knowledge. The present study demonstrated that GAS could protect hPDLSCs against LPS-induced decrease in cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Modern medical research has shown that it not only has antioxidant, anti-inflammatory, and anti-apoptotic properties, but it also improves microcirculation, protects neurons, lowers blood pressure, and prevents osteonecrosis, among other functions. Currently, gastrodin is mostly used for the treatment of cardiovascular, cerebrovascular, and neuropsychiatric diseases [9,16,[53][54][55][56] (Figure 2). decline in bone strength and mass, with age, is temporally associated with in tosis of bone cells such as osteoblasts.…”
Section: Gastrodinmentioning
confidence: 99%
“…In vivo OVX BALB/c female mice ↑Trabecular microstructure, ↑Mineral apposition rate, ↓MDA, ↑GSH [37] In vivo High glycolipid + Streptozocin SD rats ↑Trabecular microstructure, ↓MDA, ↑SOD [68] In vivo Sodium fluoride Wistar rats ↑Trabecular microstructure, ↓MDA, ↑CAT [9] In vitro LPS hPDLSCs ↑Osteogenic differentiation, ↓ROS, ↓MDA, ↓ LDH, ↑SIRT3…”
Section: Gastrodin For Osteoporosis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The PON-1 rs662 polymorphism was associated with higher enzymatic activity, which may lead to different disease susceptibility (18). Studies reported that CAT and SOD enzyme activities decreased in a fluorosis patient group compared with a control group (19,20). Studies reported evidence that coal-burning fluorosis was related to decreased SOD activity and gene expression (17,21).…”
Section: Introductionmentioning
confidence: 99%